Los manglares de Tabasco, una reserva natural de carbono - Moreno Cáliz, Elvia; Guerrero Peña, Armando; Gutiérrez Castorena, Ma. del Carmen; Ortiz Solorio, Carlos Alberto; Palma López, David Jesús (Instituto de Ecología, A.C., 2016)
The Intergovernmental Panel on Climate Change of the United Nations has indicated that carbon sequestration by plants is a low cost alternative to reduce atmospheric carbon dioxide (CO2). Forest and wetlands management could be an opportunity for carbon storage. In organic soils of mangroves, the decomposition is low leading to a high potential capacity for carbon storage. This is a reason why this ecosystem could be an alternative the carbon sequestration. The carbon stock in mangrove’s soils of Rhizophora mangle L. and Laguncularia racemosa (L.) Gaertn was quantified, in the west of Tabasco state, Mexico. The carbon storage capability was recorded to be between 47 kg C m-2 to 82 kg C m-2 which reflects the great potential of this type of soil.